The spread of financial sophistication through emerging markets worldwide - Kensinger, John W. (Research in finance, 2016)
The broad theme of Volume 32 of Research in Finance is "The Spread of Financial Sophistication Through Emerging Markets Worldwide." Contributions assess the spread of Initial Public Offerings, the use of derivatives to provide stability, corporate governance in emerging markets, and the privatization of the Russian economy. We also gain new insights into applying financial modeling in emerging markets.